Exercise Training-Increased FBXO32 and FOXO1 in a Gender-Dependent Manner in Mild Cognitively Impaired African Americans: GEMS-1 Study - Bedada, Fikru B.; Ntekim, Oyonumo E.; Nwulia, Evaristus O.; Fungwe, Thomas V.; Nadarajah, Sheeba Raaj; Obisesan, Thomas O. (Frontiers in Aging Neuroscience, 2021)
The Ubiquitin proteasome system (UPS) and FOXOs transcription factors play a pivotal role in cellular clearance and minimizing the accumulation of Aβ in neurodegeneration (ND). In African Americans (AA)s with mild cognitive impairment (MCI), the role of components of UPS and FOXOs; and whether they are amenable to exercise effects is unknown. We hypothesized that exercise can enhance cellular clearance systems during aging and ND by increasing expressions of FBXO32 and FOXO1. To test this hypothesis, we used TaqMan gene expression analysis in peripheral blood (PB) to investigate the component of UPS and FOXOs; and provide mechanistic insight at baseline, during exercise, and in both genders. At baseline, levels of FBXO32 were higher in women than in men. In our attempt to discern gender-specific exercise-related changes, we observed that levels of FBXO32 increased in men but not in women. Similarly, levels of FOXO1 increased in men only. These data suggest that a graded dose of FBXO32 and FOXO1 may be beneficial when PB cells carrying FBXO32 and FOXO1 summon into the brain in response to Alzheimer’s disease (AD) perturbation (docking station PB cells). Our observation is consistent with emerging studies that exercise allows the trafficking of blood factors. Given the significance of FBXO32 and FOXO1 to ND and associated muscle integrity, our findings may explain, at least in part, the benefits of exercise on memory, associated gait and balance perturbation acknowledged to herald the emergence of MCI.